Penegakan Hukum bagi Pelaku dan Perlindungan Hukum bagi Korban Terkait Sekstorsi dalam Tindak Pidana Korupsi berdasarkan Peraturan Perundang-undangan di Indonesia - Gan, Vannessa; Sewu, Pan Lindawaty Suherman (Bhirawa Law Journal, 2023)
In Indonesia, cases of sextortion often occur. Sextortion is the abuse of power to obtain personal gain in the form of sexual activity by coercing the victim so that the victim will experience negative impacts on health or mental health and the victim is also threatened not to report this to the authorities. Both the Sexual Violence Crime Law (hereinafter referred to as the "TPKS Law") sextortion and the Corruption Crime Law (hereinafter referred to as the "Tipikor Law") specific provisions governing sextortion still do not clearly regulate this sextortion. In the Corruption Law there are regulations regarding gratification, but this is different from sextortion. The method used is the normative juridical method, library legal research is carried out by looking at secondary data or library materials, and examining theories and cases originating from secondary legal sources. Victims of sextortion crimes need to be protected in order to fulfill victims' rights and the TPKS Law explains the protection of victims of sextortion or other sexual harassment. Victims of acts of sexual harassment have the right to receive compensation (hereinafter referred to as "Restitution") and have the right to fulfill the victim's rights, which are the state's obligation to fulfill based on the victim's condition. The rules regarding the crime of sextortion must be immediately regulated in the Corruption Law, this is so that it does not have a worse impact on society and the state.